2016
DOI: 10.1177/1558689816682092
|View full text |Cite
|
Sign up to set email alerts
|

The Journal of Mixed Methods Research Starts a New Decade

Abstract: With the past issue, The Journal of Mixed Methods Research (JMMR) has completed 10 years of publication. In celebration of JMMR's success over a full decade, and in anticipation of its journey into the future, we have decided to take the entire 11th year to celebrate and reflect. We must start with a hearty expression of gratitude to and awe of the entire mixed methods community that has come together as a field and to support the journal. From the founding and subsequent editors, to all the associate editors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 21 publications
(21 reference statements)
0
21
0
1
Order By: Relevance
“…Such a theoretical or conceptual positioning also enables authors to provide a meaningful discussion of the significance of and implications of their study (Bradbury‐Jones, Taylor, & Herber, ). Triangulation is a concept that often appears in qualitative studies, and Muir () provided an example of this within the HRD field. We include it here as a possible characteristic of rigor, but argue that it is not always appropriate or helpful, as bringing together different data sources to achieve comparison and mutual confirmation may be unsuitable where breadth and depth are prioritized (Fetters & Molina‐Azorin, ). Peer debriefing, where researchers discuss their work with disinterested peers who commit to question the research approach in a consistent and systematic fashion, is a further means to demonstrate rigor through making aspects of the research explicit as well as a critical evaluation of the patterns that are identified and the analysis process (Cho et al, 2016). For some newer scholars, the dissertation advisor might fulfill this role, and the peer review process for good‐quality journals provides a further opportunity for such procedures and challenge.…”
Section: Evaluation Criteria For Qualitative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a theoretical or conceptual positioning also enables authors to provide a meaningful discussion of the significance of and implications of their study (Bradbury‐Jones, Taylor, & Herber, ). Triangulation is a concept that often appears in qualitative studies, and Muir () provided an example of this within the HRD field. We include it here as a possible characteristic of rigor, but argue that it is not always appropriate or helpful, as bringing together different data sources to achieve comparison and mutual confirmation may be unsuitable where breadth and depth are prioritized (Fetters & Molina‐Azorin, ). Peer debriefing, where researchers discuss their work with disinterested peers who commit to question the research approach in a consistent and systematic fashion, is a further means to demonstrate rigor through making aspects of the research explicit as well as a critical evaluation of the patterns that are identified and the analysis process (Cho et al, 2016). For some newer scholars, the dissertation advisor might fulfill this role, and the peer review process for good‐quality journals provides a further opportunity for such procedures and challenge.…”
Section: Evaluation Criteria For Qualitative Researchmentioning
confidence: 99%
“…Triangulation is a concept that often appears in qualitative studies, and Muir ( 2014 ) provided an example of this within the HRD field. We include it here as a possible characteristic of rigor, but argue that it is not always appropriate or helpful, as bringing together different data sources to achieve comparison and mutual confirmation may be unsuitable where breadth and depth are prioritized (Fetters & Molina-Azorin, 2017 ). 10.…”
Section: Evaluation Criteria For Qualitative Researchmentioning
confidence: 99%
“…In response to this gap, in 2017, a multi-method study was conducted at the University of Ontario Institute of Technology (UOIT) in Oshawa, Canada, to investigate food insecurity and mental health in university students enrolled in the faculties of Health Sciences (FHS) and Education Sustainability 2019, 11, 1571 2 of 10 (FEd). A multi-method study is described as research that incorporates "all the various combinations of methods that include in a substantive way more than one data collection procedure" [14,15]. This method was proposed to facilitate a deeper understanding of food insecurity and mental health in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson, Onwuegbuzie, and Turner (2007) provide an umbrella definition of mixed methods as a type of research that "combines elements of qualitative and quantitative research approaches (e.g., use of qualitative and quantitative viewpoints, data collection, analysis, inference techniques) for the broad purposes of breadth and depth of understanding and corroboration" (p. 123). Apart from the arguments about its emergence and history (Maxwell, 2016), a wave of mixed methods research in social sciences started in the 1980s, the growth of which in the following two decades led to a turning point where the Journal of Mixed Methods Research was launched in 2007, and has continued to date (Fetters & Molina-Azorin, 2017).…”
Section: Mixed Methods Researchmentioning
confidence: 99%